Computed tomography of the spleen in chickens - Vali, Yasamin; Gumpenberger, Michaela; Konicek, Cornelia; Bagheri, Sina (Frontiers in Veterinary Science, 2023)
The avian spleen is an important immune organ in birds and its size can be used as an index of immune system responses in different conditions. Based on the lack of knowledge in computed tomography of the spleen in chickens, the present study was conducted to assess the inter- and intraobserver reliability in measurement of the spleen dimensions and attenuation, as well as the feasibility of utilization of these measurements as a predictor of different diseases. For these purposes, spleens of 47 chickens were included in the study. Two observers measured the dimensions and attenuations of the spleen which were finally compared with the clinical diagnosis. The results showed an excellent interobserver reliability in length, width and height of the spleen (ICC: 0.944, 0.906 and 0.938 retrospectively) and a good interobserver reliability was seen in evaluation of the average Hounsfield units of the spleen (ICC: 0.818). The intraobserver reliability was excellent in all the measurements (ICC>0.940). Additionally, no statistical differences were detected in the spleen size and attenuation between the normal and diseased groups. Based on the present results the computed tomographic measurements of the spleen could not predict the clinical diseases of the chickens; however, the low rates of the inter/ and intraobserver variability suggests the reliable utilization of these computed tomographic measurements in routine clinical application and follow-up examinations.